Revelations from story writing in business statistics: An exercise in decoding - Lemieux, Collette; Quiring, Brad (Journal of University Teaching and Learning Practice, 2021)
This paper describes our experiences with implementing an innovative approach to decoding our discipline, which involves writing dialogue-driven stories that explore authentic, context-rich problems within introductory business statistics. Our paper begins by introducing the decoding model created by Middendorf and Pace (2004). We then explain why we initially chose to write pedagogical stories as a meaningful way to deliver our course material, later discovering that the process also served as an alternative means of decoding our discipline. The discussion focuses on our case study, which investigates how the process of writing stories lead to significant benefits for ourselves as instructors. In particular, we connect our learning experiences to Middendorf and Pace’s (2004) work on decoding the discipline, which utilizes a seven-step process to help faculty members interrogate their teaching processes for bottleneck concepts. We present our reflections on how the process of writing stories acted as an effective alternate means of decoding the discipline.